Pemanfaatan Limbah Minyak Jelantah Untuk Pembuatan Lilin Aromaterapi dan Lilin Hias Sebagai Upaya Pemberdayaan Ekonomi Masyarakat Kelurahan Kalimulya, Depok, Jawa Barat - Nuriskasari, Isnanda; Mafendro Dedet Eka Saputra, Yuli; Nainggolan, Benhur (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2022)
Kalimulya Depok Village requires a program to utilize household waste for community economic empowerment. Used cooking oil is one of the household wastes that have a hazard to health and the environment. Therefore, the team lecture of Program Study Energy Conversion Engineering Technology PNJ carried out community service with the theme of using used cooking oil waste into aromatherapy candles and decorative candles. This activity consisted of presenting material related to the dangers of used cooking oil and the procedure for making aromatherapy candles and decorative candles from used cooking oil, then continued with the practice of making aromatherapy candles and decorative candles from used cooking oil. The survey results show an increase in the knowledge and skills of the trainees regarding the process of making aromatherapy candles and decorative candles from used cooking oil.